The Tradition of Batajak Rumah and the Strengthening of Multicultural Attitudes in Islamic Religious Education Learning in Junior High Schools in Balangan Regency - Murjiah Murjiah; Zulfa Jamalie (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study examines the tradition of Batajak Rumah, a communal practice of building houses through mutual cooperation in Banjar society, and its role in strengthening multicultural attitudes among junior high school students in Balangan Regency, South Kalimantan. Balangan Regency is a multiethnic region inhabited by Banjar, Dayak Meratus, Javanese, Bugis, and other ethnic communities. Using a library research approach with ethnopedagogical analysis, this article argues that Batajak Rumah inherently embodies five multicultural values: cross-ethnic ta'awun (mutual assistance), ukhuwwah insaniyyah (human brotherhood), social reciprocity, participatory inclusiveness, and leadership based on expertise rather than ethnicity. These values have direct correspondence with Islamic Religious Education (PAI) teachings and can be strengthened through four learning strategies: inductive thematic integration, experiential learning, digital documentation projects, and collaboration among schools, communities, and families. The findings indicate that Batajak Rumah is an active pedagogical asset that can optimize the role of PAI learning in shaping multicultural attitudes among junior high school students in multiethnic areas, while also enhancing the relevance and contextualization of PAI as a character-building subject.